2017
DOI: 10.1002/cepa.203
|View full text |Cite
|
Sign up to set email alerts
|

07.13: On extending the direct strength method to the design of cold‐formed steel built‐up columns

Abstract: This paper presents a numerical investigation of the effects of discrete fasteners on the buckling behaviour of cold-formed steel (CFS) built-up columns and concludes with the assessment of the applicability of the current direct strength method (DSM) to the design of these members. To this end, the compound strip method is first utilised to accurately model the buckling behaviour of CFS built-up columns under axial compression via introducing connecting elements to represent the contribution of discrete faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The tests suggested that some degree of composite behaviour was present. Abbasi et al [9] further investigated this built-up geometry by carrying out a stability analysis using the compound strip method to study the effect of the connector spacing on the buckling behaviour of the columns, and showed that reducing the connector spacing enhanced the elastic local and global buckling stresses of the built-up member.…”
Section: Introductionmentioning
confidence: 99%
“…The tests suggested that some degree of composite behaviour was present. Abbasi et al [9] further investigated this built-up geometry by carrying out a stability analysis using the compound strip method to study the effect of the connector spacing on the buckling behaviour of the columns, and showed that reducing the connector spacing enhanced the elastic local and global buckling stresses of the built-up member.…”
Section: Introductionmentioning
confidence: 99%